Two new and exceptional poison dart frogs of the genus Dendrobates (Anura: Dendrobatidae) from the Northeastern Flank of the cordillera Central of Colombia - Rueda-Almonacid, José Vicente; Rada, Marco; Sánchez-Pacheco, Santiago J.; Velásquez-Álvarez, Álvaro Andrés; Quevedo, Alonso (Zootaxa, 2006)
We name and describe two new species of poison dart frogs of the genus Dendrobates, from the northeastern flank of the cordillera Central in the departamentos de Tolima and Caldas. Those frogs share an exceptional synapomorphy within the family, which consists of a first toe reduced and fused with the second toe, allowing only four toes to be seen externally. Perhaps this unusual characteristic is reason to create a new genus within the Dendrobatidae, however, this must await a period of further investigation of the phylogeny of these two species, including a molecular and  anatomic analysis. Elucidating the taxonomic position of these species and the naming a new genus, if found to be appropriate and applicable, will be the subject of a future manuscript.